(untitled) (Bangladesh Journal of Agricultural Research, 2016)
A series of field experiments were conducted at farmers fields under Ganges Tidal Floodplain (AEZ-13) during 2012-2014 to identify suitable fertilizer management practices for maximizing rice yield. The treatments were: T1 = AEZ basis BRRI recommended fertilizer dose (BRRI dose), T2 = Rice Straw (RS)/Cowdung (CD) + IPNS (Integrated Plant Nutrition System) basis fertilizer management (RS/CD+IPNS) and T3 = Farmers Practice (FP). BRRI dhan27 (T. Aus), BRRI dhan49 and BRRI dhan54 (T. Aman) and BRRI dhan29 and BRRI dhan47 (Boro) were used as test varieties of rice. All fertilizers except urea were applied at final land preparation. In T. Aus and T. Aman seasons, urea was applied in two equal splits as FP. In Boro season, urea was added in three equal splits as FP. Urea Super Granule (USG) was applied at 12-15 DAT for T1 and T2 treatments. Treatment RS + IPNS gave 19-27% higher grain yield over FP and it saved full dose of K and S and partial dose of P fertilizer. Treatment CD + IPNS gave a 10-16% higher grain yield over FP and it saved full dose of P, K and S fertilizer in T. Aus and T. Aman seasons. On the other hand, BRRI recommended fertilizer dose gave 7-15% higher grain yield over FP. Bangladesh J. Agril. Res. 41(4): 667-673, December 2016